Linguistik Generatif-Transformatif Noam Chomsky dan Implementasinya dalam Pembelajaran Bahasa Arab - Zuhrotus Saniyyah; Sovia Sovia; Nayla Hikmah Khoirun Nisa; M Yunus Abu Bakar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Arabic language instruction in various educational institutions today is still dominated by the structuralist paradigm, which emphasizes the mechanical memorization of patterns and repetition without addressing aspects of linguistic creativity. This study aims to explore the essence of Generative-Transformational Linguistic Theory proposed by Noam Chomsky and to formulate innovative ways to implement it in Arabic language learning. The approach taken in this study is qualitative, specifically a literature review (library research). Data were collected through primary and secondary literature, which were then examined using content analysis methods through the steps of simplification., categorization, and interpretation. The research findings indicate that Generative-Transformative Theory shifts the focus of learning from imitation to creation through the use of the Language Acquisition Device (LAD). Through the dichotomy of deep structure and surface structure, students are guided to perform various transformational operations such as substitution (al-ibdal), expansion (al-ittisa’), elision (al-hadzf), and addition (al-ziyadah). This principle is also found to align with the classical linguist Ibn Jinni’s thoughts on the concepts of Asl and Furu’. This research suggests that teachers of grammar and word structure should change how they teach strategies into a cognitive-creative process that enables students to independently and authentically generate an unlimited number of new utterances.